PENINGKATAN KINERJA GURU DALAM MENETAPKAN KRITERIA KETUNTASAN MINIMAL MELALUI WORKSHOP DI SDN 091620 PERDAGANGAN - Marsal, Benni (Jurnal Tematik, 2020)
Improving Teacher Performance in Setting Minimum Completeness Criteria (KKM) ThroughWorkshop at Sdn 091620 Trade. The purpose of this study was to improve the ability of teachers to setMinimum Completeness Criteria (KKM) through the implementation of workshops at SDN 091620Perdaganga. This research is an action research, the subject of this research is the Principal and Teachersof State Elementary School 091620 Trade totaling 7 people, consisting of 1 principal and 6 classteachers. The teacher determines the Minimum Completeness Criteria. From the data analysis of theresults of the observation and evaluation of the ability to compile the KKM skills in cycle I for thepercentage of classical completeness achievement of 42.8% while in cycle II it becomes 100%; there isan increase of 19.96%. When viewed from the indicators performance for evaluation of the knowledgeskills of teachers in compiling KKM can be said to be successful because it has reached the idealpercentage for absorption of 75 and completeness of 85%. Looking at the data above it can be said thatthe indicators of the expected / outcome variables and the action variables have been achieved. has beenable to improve the ability of teachers-g uru at SD Negeri 091620 Perdagangan in analyzing andcompiling KKM